2007
DOI: 10.1016/j.anbehav.2007.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines influence aggressiveness in crayfish but not their force or hierarchical rank

Abstract: This study aimed at understanding the influence of biogenic amines on the agonistic behaviour of the crayfish Procambarus clarkii, a model organism for crustacean decapods. Specifically, we investigated whether the hierarchical rank of fighting individuals might be altered by injecting solutions of either serotonin or octopamine into their haemolymph. First, we assessed the effect and duration of the bioamines on the behaviour, posture, and chelar force of 60 adult males paired for size. Then, we examined thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
4
14
0
Order By: Relevance
“…Consequently, the percentage of lost bouts was not significantly increased after 5-HT injection. Conversely, the percentage of wins was not increased in smaller injected crayfish, as previously observed in another study (Tricarico and Gherardi, 2007). In all cases, 5-HT was able to postpone decision making without significantly inverting the outcome of the bouts.…”
Section: -Ht Differentially Modifies Aggression and Decision Makingsupporting
confidence: 82%
See 1 more Smart Citation
“…Consequently, the percentage of lost bouts was not significantly increased after 5-HT injection. Conversely, the percentage of wins was not increased in smaller injected crayfish, as previously observed in another study (Tricarico and Gherardi, 2007). In all cases, 5-HT was able to postpone decision making without significantly inverting the outcome of the bouts.…”
Section: -Ht Differentially Modifies Aggression and Decision Makingsupporting
confidence: 82%
“…By contrast, the inverse interpretation generally prevails in crustaceans, as it has been demonstrated that 5-HT increases aggressive motivation and delays the decision to stop fighting (Huber et al, 1997;Huber and Delago, 1998;Herberholz, 2014). However, conflicting observations have also been described in these animals (Peeke et al, 2000;Panksepp et al, 2003;Tricarico and Gherardi, 2007). Moreover, in insects, the effects of 5-HT appear to vary in different species: in crickets, 5-HT is able to decrease aggression and favor escape behavior (Stevenson and Rillich, 2012;Stevenson and Schildberger, 2013), but in ants, aggressiveness is weakly affected by exogenous 5-HT (Szczuka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the effects known of amines on aggressive motivation, the mechanisms underlying winner and loser effects are still poorly understood. In crayfish and crabs, the injection of serotonin or octopamine into dominant and subordinate animals modifies aggressiveness during the following encounters but fails to reverse previous hierarchical rank in [25], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…In the crab Neohelice granulatus (formerly Chasmagnathus ), the level of aggressiveness is a major factor in the outcome of a fight and can be increased with release of serotonin 3 . Serotonin has also been shown to increase aggressive behaviour in lobsters 4 and crayfish 5 , although this does not shift their dominance rank. However, other research has shown a decrease in aggressiveness after serotonin injection in crayfish 6 .…”
mentioning
confidence: 99%